2022
DOI: 10.1177/03080226221121745
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of combining robotic therapy and modified constraint-induced movement therapy for moderate to severe upper limb paresis after stroke in subacute phase: Case–control study by propensity score analysis

Abstract: Introduction: Robotic assisted therapy and modified constraint-induced movement therapy are used evidence-based approach in stroke rehabilitation. However, there is no study showing a combination of robotic assisted therapy and modified constraint-induced movement therapy (combined therapy) in the subacute phase. This study investigated the effectiveness of combined therapy in stroke patients with moderate to severe upper limb paresis compared with conventional occupational therapy at subacute setting. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recently, robotic therapy has been introduced and its efficacy has been reported in cases where patients presented with moderate to severe paralysis with FMA <30 during the convalescent period ( 49 ). Furthermore, case–control studies have reported favorable results with TOT with robotic therapy combined ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, robotic therapy has been introduced and its efficacy has been reported in cases where patients presented with moderate to severe paralysis with FMA <30 during the convalescent period ( 49 ). Furthermore, case–control studies have reported favorable results with TOT with robotic therapy combined ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients received interventions for upper extremity hemiplegia based on guidelines (Winstein et al, 2016). Robotic-assisted therapy and modi ed Constraintinduced movement therapy were mainly provided for UE functional training following the protocol from the developer and promoted real-world arm use in the affected hands (Morris et al, 2006;Anmoto et al, 2023). DTI acquisition DTI was performed using a 3.0-T magnetic resonance scanner (Trio; Siemens AG, Erlangen, Germany) with a 16-channel head coil.…”
Section: Introductionmentioning
confidence: 99%